Proceedings of the 12th International Web for All Conference 2015
DOI: 10.1145/2745555.2746658
|View full text |Cite
|
Sign up to set email alerts
|

Measuring text simplification with the crowd

Abstract: Text can often be complex and difficult to read, especially for peo ple with cognitive impairments or low literacy skills. Text simplifi cation is a process that reduces the complexity of both wording and structure in a sentence, while retaining its meaning. However, this is currently a challenging task for machines, and thus, providing effective on-demand text simplification to those who need it re mains an unsolved problem. Even evaluating the simplicity of text remains a challenging problem for both compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Our cloze results support the claim in [9] that untrained speakers can implicitly judge sentence difficulty in agreement with expert judgments, but imperfectly so. Moreover, perceived difficulty, as measured by the sentence comparison task somewhat similar to that in [9], is not clearly related to cloze scores on the same sentences. This suggests that actual and perceived difficulty do not measure identical sentence attributes.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our cloze results support the claim in [9] that untrained speakers can implicitly judge sentence difficulty in agreement with expert judgments, but imperfectly so. Moreover, perceived difficulty, as measured by the sentence comparison task somewhat similar to that in [9], is not clearly related to cloze scores on the same sentences. This suggests that actual and perceived difficulty do not measure identical sentence attributes.…”
Section: Discussionsupporting
confidence: 84%
“…Experience with simplifications in the Simple English Wikipedia suggests that non-professional simplification is much less reliable than that obtained from professionals [2]. However, [9] showed that crowd-source methods could accurately rate the number of simplifying transformations made to single complex sentences. These results, from a slightly smaller set of sentences, are most directly comparable to the results reported above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations